Status Penyelesaian Piutang Bank BUMN: Komparasi Putusan Mahkamah Konstitusi No.77PUU-IX/2011 dan Putusan Mahkamah Konstitusi No.48/PUU-XI/2013 - Saputra, Raden Ismail Alam (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The State Finance Law has made BUMN entities as state institutions, not as business entities, therefore in the practice of managing BUMNs they are often trapped in a dilemmatic position, whether BUMN assets in relation to state finances are subject to the state financial regime or become subject to state finances. corporate regime (limited liability company). In terms of managing receivables, receivables from state-owned banks are classified as state receivables so that they are submitted to the State Receivables Affairs Committee. In fact, in accordance with the explanation of Article 4 paragraph (1) of the BUMN Law, the receivables contained in BUMN as a result of the agreement carried out by BUMN as a corporate entity are no longer seen as state receivables. The problem then got a bright spot after the Constitutional Court Decision No. 77/PUU-XI/2011 which issued BUMN bank receivables from state receivables, because BUMN assets were considered separate from state assets. However, in the Decision of the Constitutional Court Number 48/PUU-XI/2013 the Constitutional Court ruled that the status of state assets that are invested in SOEs remains part of state finances. Then what is the real status of the wealth of state-owned banks originating from the state's participation? This study found a contradiction between two decisions of the Constitutional Court which resulted in legal certainty of the wealth status of state-owned banks.